Pengaruh Harga Dan Kepuasan Pelanggan Terhadap Keputusan Pembelian Ulang Jasa Pengiriman Barang Pada Pt. Wahana Di Kota Banda Aceh - Desi Aggraini (SUMBER INFORMASI MANAJEMEN BISNIS DAN AKUNTANSI, 2024)
The purpose of this study was to determine the partial and simultaneous influence of price and customer satisfaction on repurchase decisions for goods delivery services at PT. Wahana in Banda Aceh. The author employed a quantitative research method, with a sample size of 100 consumers using purposive sampling and multiple linear regression analysis using SPSS 17.0 software. The results showed that price and customer satisfaction significantly influenced repurchase decisions for goods delivery services at PT. Wahana in Banda Aceh. The implication of this study is that price and customer satisfaction significantly influence repurchase decisions for goods delivery services at PT. Wahana in Banda Aceh. This is because affordable prices will easily attract customers to use competitive services, and customer satisfaction will be met with timely delivery.